Performance Appraisal and Promotion Practices of Public Commercial Banks in Bangladesh- A Case Study on ACR Method - Anjum, Nishath; Rahman, Md. Mashfiqur (SEISENSE Journal of Management, 2021)
Purpose- Performance appraisal is crucial for enhancing the productivity of employees working in any sector. This paper investigates the prevailing performance appraisal system and promotion policy of selected public commercial banks (Sonali Bank Ltd, Rupali Bank Ltd, and Agrani Bank Ltd) in Bangladesh. Design/Methodology- The study is a descriptive case of three banks. The researchers interviewed six experienced banking professionals who provided rich data about their respective banks' performance appraisal and feedback systems. The findings of the study are based on the thematic analysis of the respondents’ statements. However, the study also utilized secondary sources for other relevant information. Findings- The study found that all the banks have an established system for evaluating employee performances through ACR with structured criteria for the promotion. The standard criteria include ACR, academic degree, banking diploma, length of service, etc. However, the grading scale for promoting to different positions is differing among the banks. The study also addressed some limitations of the ACR method as rating only by the manager, biasness on ratings, no appraisal feedback to employees etc. Practical Implications- The study seeks to drive the attention of policymakers to utilize their existing performance appraisal system better and design a more effective one with a well-established promotion policy to encourage the employees to give their best effort at the workplace.